Analisis Kriminologi Kualitatif Pengaruh Media Sosial terhadap Pola Kejahatan Siber Remaja - Kurnia Rahmasari; Radityo Wirananto; Aghastyar Aghastyar; Giovano Allan Loway; Pietro Grassio Ekoyulio (CV. AFDIFAL MAJU BERKAH, 2026)
The rapid development of social media has transformed patterns of social interaction among urban youth while simultaneously creating new opportunities for cybercrime. Social media functions not only as a communication platform but also as a digital environment where values, behaviors, and social identities are constructed. This study aims to analyze the influence of social media on cybercrime patterns among urban Indonesian youth through a qualitative criminological approach. The research employs a qualitative method with descriptive-analytical specifications using a literature-based approach. Data were collected from academic journals, books, research reports, and relevant legal documents and analyzed through qualitative content analysis. The findings reveal that social media significantly contributes to the emergence of cybercrime patterns among urban youth, particularly in the forms of cyberbullying, hate speech, online fraud using fake accounts, dissemination of personal data, and basic hacking activities. The study also identifies three major criminogenic factors underlying cybercrime involvement: individual factors, including low digital literacy, weak self-control, and the need for social recognition; social factors, including limited parental supervision, inadequate digital education, and strong peer-group influence; and structural factors, including widespread internet access, weak perceptions of law enforcement effectiveness, and the anonymity provided by digital platforms. Furthermore, the findings indicate that many young people engage in cybercrime not primarily for economic gain but due to curiosity, experimentation, online popularity, and peer pressure. Social media also facilitates the formation of online subcultures that normalize and reinforce deviant behavior through continuous interaction and social validation.This study concludes that cybercrime among urban Indonesian youth is a multidimensional phenomenon resulting from the interaction of individual, social, and structural factors within digital environments. Therefore, effective prevention requires integrated strategies involving digital literacy enhancement, family and school-based social control, ethical digital education, and adaptive cybercrime policies that respond to technological developments.